Pattern distribution of abnormal hemoglobin variants by cation exchange High Performance Liquid Chromatography: a study of 9,116 subjects - Gamit, Sejal Kalyanbhai; Nishal, Arpita; Shah, Pinal; Patel, Archana (International Journal of Research in Medical Sciences, 2019)
Background: The present study was conducted to identify pattern distribution of abnormal haemoglobin variants by using HPLC method in a tertiary care hospital, Surat, Gujrat, India. Methods: A cross sectional study of one-year duration was conducted including 9,116 patients screened for the presence of abnormal haemoglobin variants. Blood samples were initially tested for solubility test and run on automated haemoglobin analyzer for complete haemogram. All the suspected and family study cases were processed for HPLC (Bio-Rad Variant II) for conclusive diagnosis. Patients with a history of recent blood transfusion of less than 3 months duration were excluded from the study. Results: A total of 9,116 cases (1390 males, 7726 females) were included in the present study. The age group of patients ranged from 1 month to 95 years. Solubility test and complete haemogram were performed in all the cases. Out of the 9,116 cases, 8409(92.24%)cases had normal HPLC pattern. 492(5.40%)cases were diagnosed as sickle cell trait, 176(1.93%) cases as sickle cell disease, 29(0.32%) cases as β thalassaemia trait, 1(0.01%) case as β thalassaemia major, 2(0.02%)cases as Hb E heterozygous and 03 (0.07%) cases as Hb D Punjab heterozygous. One case of double heterozygous for Hb E-β thalassaemia was also found. Conclusions: HPLC is a rapid, accurate and useful method for diagnosing haemoglobinopathies. It serves as an reliable tool in diagnosing the presence of abnormal haemoglobin variants in suspected cases on routine haematology in developing countries like India, where the resources for detection of haemoglobinopathies are limited. Early diagnosis may help in proper management of patients.